The biasing nature of gang evidence: inducing memory errors for evidence of past criminal behavior - Eisen, Mitchell (Psychology, crime & law, 2025)
Two experiments were conducted to examine the effects of introducing gang evidence on jurors’ memory of the evidence and decision-making. In Experiment 1, 234 participants viewed a staged trial. The evidence against the defendant was weak and consisted of a single tentative eyewitness identification. Half of the participants viewed a version of the trial in which the defendant was described as a dangerous gang member, and half viewed the trial with no mention of gangs. Those who heard the gang testimony were significantly more likely to falsely recall hearing evidence that was never presented describing the defendant’s previous criminal conduct and convictions for similar crimes. The second experiment (N = 328) was conducted online to secure a more diverse national sample. The results replicated, as those in the gang condition were significantly more likely to falsely remember hearing testimony about the defendant’s criminal history and to find the defendant guilty.